Analisis Pentingnya Literasi Digital ASN dalam Mendukung Digitalisasi Pelayanan Publik di Indonesia - Khansalaili Hasna Wibawati; Frigia Amasia (Musamus Journal of Public Administration, 2024)
Digital Literacy is a critical aspect in this era of massive technological development. Especially regarding digital transformation in Indonesia, which is currently echoed by the government as a positive step in shaping excellent public services. However, various problems are still found, including the low competence of civil servants in the field of technology, differences in civil servant’s perspective on technology, and a limited budget. State civil apparatus who play an important role in providing public services to the community must be able to have digital literacy skills so that the services provided run optimally. Therefore, the government is expected to pay attention to the digital literacy aspect of civil servant’s through education, training, and providing access to support for technological infrastructure.